2019
DOI: 10.1002/chem.201806204
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Properties of Organometallic Molecular Cylinders Bearing Bulky Imidazo[1,5‐a]pyridine‐Based N‐Heterocyclic Carbene Ligands

Abstract: The metal-controlled self-assembly of organometallic molecular cylinders from as eries of imidazo[1,5-a]pyridine-based tris-NHCl igandsi sd escribed in this report. The imidazo[1,5-a]pyridinium salts H 3 -L(PF 6 ) 3 (L = 4a-4c)w ere treated with 1.5 equivalents of Ag 2 Ot oy ield the trinuclear Ag I hexacarbene cages [Ag 3 (L) 2 ](PF 6 ) 3 (L = 4a-4c), in which three Ag I are sandwiched between the two tricarbene ligands. The silver(I)c omplexes [Ag 3 (L) 2 ](PF 6 ) 3 underwent a facile transmetalation reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…While if the architecture is an interlocked cage, the α-imidazole peaks are expected to split in a 1 : 1 ratio as observed. 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While if the architecture is an interlocked cage, the α-imidazole peaks are expected to split in a 1 : 1 ratio as observed. 27 …”
Section: Resultsmentioning
confidence: 99%
“…These dimensions indicate that 1 has an internal cavity big enough to accommodate guest molecules. 27 This was unique as interlocked structures generally do not have internal cavity big enough for guest encapsulation. 29 …”
Section: Resultsmentioning
confidence: 99%
“…In order to increase the internal cavity, our group recently designed and synthesized a variety of imidazo [1,5-a]pyridine-based tris-NHC ligand precursors. For example, as shown in the Scheme 32, the cylinder-like trinuclear silver(I) hexacarbene complex 46-Ag was obtained in 73% yield from the imidazo [1,5-a]pyridinium salt L31a and Ag 2 O in acetonitrile (Scheme 32) [87]. In spite of an ideal separated distance ( 7 Å) of central phenyl rings for the potential formation of interlocked cages, the formation of a triple interlocked structure was prevented due to possible steric hindrance from the central phenyl and its three attached phenylene groups, and the torsional twisting conformation they formed.…”
Section: Scheme 30 Synthesis Of Ploy-nhc-agmentioning
confidence: 99%
“…The distance be- tween the two triphenylene planes of the cage is 7.05 Å, so the recognition of coronene was observed based on π-π stacking interactions and a perfect dimensional match (Figure 5) [81]. Recently, Han et al [87] reported that organometallic cylinder-like assemblies featuring a cavity were able to accommodate dimethyl sulfoxide through host-guest interactions.…”
Section: Host-guest Chemistrymentioning
confidence: 99%
“…Over the last few decades, metallosupramolecular assemblies have drawn much attention due to their diverse molecular topologies, novel physical/chemical properties, and numerous potential applications. Among these appealing architectures, metallosupramolecular assemblies featuring poly-N-heterocyclic carbene (NHC) ligands have become an interesting target during the past decade due to their outstanding catalytic applications that are afforded by the intrinsic metal–carbene bonds. Various two-dimensional and three-dimensional NHC-based metallosupramolecular assemblies were constructed from polydentate NHC ligands and coinage metals (Ag I , Au I ), in which the metals were usually sandwiched between two NHC ligands with highly symmetrical structures. Although the fixed linear geometry of the C NHC –M–C NHC bond enables the formation of architectures with predictable topologies, it also limits the diversity of NHC-based metallosupramolecular architectures.…”
Section: Introductionmentioning
confidence: 99%